Beragama yang Fanatik Tanpa Sikap Ekstrem - Amsal Bakhtiar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2005)
In religion, there are at least two variables, namely ‘fanaticism’ and ‘extremism’, which can be analyzed into four groups: first, non-extreme fanatics; second, extreme fanatics; third, non-fanatics but extreme; fourth, neither fanatics nor extreme. The focus of this paper is on religious fanaticism without extremism and efforts to realize it. Fanaticism here refers to devout and obedient religious attitudes in performing worship, which are manifested in individual and social life. Meanwhile, extremism in this context refers to a more literal, ideological, and exclusive religious attitude. This exclusivity can ultimately lead to religious communalism and the politicization of religion, so that what emerges is not the true essence of religion, but a religion that has been wrapped in the ideology of certain political parties and ethnicities. The root of the problem of extremism is not only in terms of religion, but also politics, economics, social issues, and so on.